ZnO/Zn/Amorphous Carbon Matrix Nanostructured Composite Powder: a New Photocatalyst for Dye. Issue 19 (28th December 2015) - Lanfredi, Silvania; Silveira, Gisele S.; Potensa, Bruno S.; Nobre, Marcos A. L
ABSTRACT: Both synthesis and photocatalytic potential of an innovative catalyst-powder type composite material based on the Zn or/and ZnO dispersed in a matrix of amorphous-carbon have been investigated. Zn/ZnO/amorphous-carbon nanostructured-matrix composite was prepared by partial pyrolysis method based on the Pechini method. The amorphous character of composite was characterized X-ray diffraction, while chemical bond investigated by infrared spectroscopy. The photocatalytic activity directed to the degradation of the phenol red dye of small fraction of commercial ZnO, Zn/C and Zn/ZnO/C composites were evaluated as a function of the degradation reaction of the phenol red dye, in the alkaline medium pH = 9. A mass concentration of 1:10, 000 was selected being considered 30 and 150 min of reaction A comparison between photocatalytic activity showed that the degradation rate of phenol red dye is more efficient at both ZnO/Zn/C and Zn/C amorphous composites when compared to the pristine ZnO. The efficiency obeys the following order C/Zn ≥ C/ZnO/Zn > commercial ZnO with conversion equal to 70% for C/Zn and C/ZnO/Zn, while for the ZnO is around 55%. The kinetic of degradation is discussed.